Options for Meeting the Maintenance Demands of Active Associate Flying Units - Drew, John G. (RAND Corporation, 2008)
RAND developed a methodology to help understand and explain the differences between U.S. Air National Guard and active component aircraft maintenance productivity. This research focuses on maintenance options for supporting associate units, where the goal of the associate unit is to produce trained pilots in the most efficient manner possible.